Abducens nerve palsy as initial symptom of trigeminal schwannoma. Issue 12 (December 1977) - Yamashita, J; Asato, R; Handa, H; Nakao, S; Ogata, M
Abstract : The insidious onset and slow progression of symptoms may cause delay in the recognition of trigeminal schwannomas. Two cases with abducens nerve palsy as an initial symptom are reported, in both of whom the tumour was growing mainly below and anterior to the intracavernous portion of the internal carotid artery. Early detection of clinical symptoms and thorough radiological investigations are important in the early diagnosis of these lesions.